Conceptual coup of the sovereign immunity: the law of Jasta as a model - الفتلاوي احمد عبيسي (Journal of Legal Sciences, 2018)
The research focused on important legal issues that have been formulated in questions such as: What is the concept of immunity and what is its purpose? , In other words immunity from whom? In what circumstances? We also ask ,Does sovereign immunity principle , apply as absolute doctrine or have limitations been dealt with in national jurisdiction? On the question of what are the grounds for the distinction and partnership between the concept of sovereign immunity and the concept of diplomatic immunity? Has sovereign immunity been affected by the pursuit of grave and terrorist violations, in particular, contrary to what international practices have been in the past as a sanctuary in which states and officials are protected from any criminal or civil prosecution? Will the American Act (the Justice Against sponsors of terrorism Act change the sovereign states immunity principle? What are its effects at the national (American) and international levels?